Fluorinated coatings and finishes handbook the definitive user's guide - McKeen, Laurence W. (William Andrew, an imprint of Elsevie, 2016)
Fluorinated Coatings and Finishes Handbook: The Definitive User's Guide, Second Edition, addresses important, frequently posed questions by end-user design engineers, coaters, and coatings suppliers on fluorinated coatings and finishes, thus enabling them to achieve superior product qualities and shorter product and process development times. The book provides broad coverage of these fluorinated polymer coatings, including the best known PTFE, polytetrafluoroethylene, first trademarked as Teflon and ePTFE (GoreTex). Their inherent qualities of low surface tension, non-stick, low friction, high melting point, and chemical inertness make fluoropolymer coatings widely desirable across thousands of industrial and consumer applications, but these properties also make it difficult to convert fluoropolymers to coatings that have sufficient adhesion to the substrate to be protected. In this book, readers learn how fluoropolymer coatings are used and made, about their pigments and fillers, binders, dispersion processes, additives, and solvents. The book includes substrate preparation, coating properties, baking and curing processes, performance tests, applications, and health and safety
Includes bibliographical references and index
Keywords: TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Fluoropolymers; Plastic coatings; Plastic coatings -- Handbooks, manuals, etc; Fluoropolymers -- Handbooks, manuals, etc